Das muskelinvasive und metastasierte Urothelkarzinom der Harnblase: Aktueller Stand histopathologischer, molekularer und immunologischer Prognose- und Prädiktionsfaktoren - Bertz, Simone; Bahlinger, Veronika; Lange, Fabienne; Hartmann, Arndt; Eckstein, Markus (Die Pathologie, 2024)
Background: Muscle-invasive and metastatic urothelial carcinoma (UC) represents a heterogeneous disease entity with numerous morphological, molecular, and immunological phenotypes. Aims: This article aims to provide an overview of current histopathological, molecular, and immunological prognostic and predictive factors in muscle-invasive and metastatic UC. Results and discussion: Muscle-invasive and metastatic UC exhibits a wide range of divergent differentiations and histological subtypes. The correct diagnosis of these morphological variants is essential, as they may determine the clinical course and may also present specific and potentially therapeutically targetable molecular alterations (e.g., HER2 alterations in micropapillary UC). The morphological subtypes largely correlate with the six molecular consensus subtypes. Furthermore, morphological and molecular subtypes are associated with immunological properties that are relevant for modern immunotherapies, such as the PD-L1 status. Numerous immunotherapy studies in the setting of curatively treatable muscle-invasive UC will be reported in 2024 and 2025, likely leading to an increasing number of PD-L1 testing indications.
CRIS-Team Scopus Importer:2024-08-16
Keywords: B7-H1 antigen; Disease progression; Immunotherapy; Molecular pathology; Transitional cell carcinoma